2010
DOI: 10.17221/158/2009-pse
|View full text |Cite
|
Sign up to set email alerts
|

Salt tolerance evaluation and relative comparison in cuttings of different omegranate cultivar

Abstract: A pot experiment was conducted during a two-year period in order to evaluate and compare the salinity tolerance of 10 Iranian commercial cultivars of pomegranate. Pots were arranged in a split plot design with two factors included water salinity as main plot in 3 levels of 4, 7 and 10 dS/m and 10 pomegranate cultivars as sub-plot and 3 replications. The properties concerned during the experiment were vegetative growth, percentage of alive cuttings after 2 month and the necrosis and chlorosis of leaves. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 15 publications
4
23
0
Order By: Relevance
“…An excess of Na + disturbs cellular ion homeostasis, and leads to other effects such as interference in enzyme activities and oxidative stress (Afzal et al 2008, Okhovatian-Ardakani et al 2010). Cl -is the most prevalent anion under saline conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An excess of Na + disturbs cellular ion homeostasis, and leads to other effects such as interference in enzyme activities and oxidative stress (Afzal et al 2008, Okhovatian-Ardakani et al 2010). Cl -is the most prevalent anion under saline conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Salt stress is recognized as a major factor that limits plant growth, physiology and productivity, mainly by inducing osmotic effects, ion-specific effects and oxidative stress (Okhovatian-Ardakani et al 2010). Moreover, membrane stability, chlorophyll biosynthesis, carbon and nitrogen metabolism and rates of photosynthesis and respiration are also seen to be significantly hampered due to high salinity (Ashraf 2004).…”
mentioning
confidence: 99%
“…The lower RWC of NaCl-treated pomegranate leaves reflected the impairment in the capacity of water retention [25], which caused stomatal closure, then reduced the rate of photosynthesis and transpiration. A potentially negative effect of reduction in Pn and leaf area was the decreased total CO 2 assimilation and thus inhibited plant growth and development under saline conditions [24,26]. Consequently, the limited vegetative growth resulted in a smaller pomegranate plant with shorter shoots.…”
Section: Growth and Physiological Parameters Of Pomegranate Cultivarsmentioning
confidence: 99%
“…The pomegranate has the reputation of being highly adaptive to a wide range of climate, water and soil conditions . It is considered moderately tolerant to salinity (Maas, 1993;Allen et al, 1998;Naeini et al, 2004); however, the mode and magnitude of the plant response to salinity are cultivar dependent (Naeini et al, 2006;Okhovatian-Ardakani et al, 2010). Based on the results of our earlier study on the evapotranspiration, crop coefficient and growth of two young pomegranate varieties under salt stress we have suggested that the term moderately sensitive to salinity more adequately describes the crop (Bhantana and Lazarovitch, 2010).…”
Section: Introductionmentioning
confidence: 96%